Pengaruh Kinerja Keuangan Dan Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan Pada PT. Bank Central Asia Tbk Periode 2015-2024 - Nurhidaya Safitri; Muhammad Nur Abdi; Sahabuddin (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of financial performance and Corporate Social Responsibility (CSR) on company value at PT. Bank Central Asia Tbk during the 2015-2024 period. The research method used is quantitative with a documentary study approach and multiple regression analysis to test the relationship between variables. The results of the study indicate that financial performance has a significant positive effect on company value, as well as CSR which makes a positive contribution to increasing stakeholder trust and the company's reputation. This finding confirms the importance of synergy between financial performance and social responsibility in increasing corporate value in the Islamic banking sector. The implication of this study is that companies need to continue to improve financial performance while optimizing CSR programs as a strategy to maintain and increase corporate value.